Working Platform Design of Welding System based on Flexible Modal Analysis - Zhao Ting; 2Liu Geng; Zhang Zhanzhi; Ni Jiangtao; Tong Kewei (Jixie chuandong)
According to the requirements of tank bottom longitudinal seam welding system of the new generation launch vehicle,its working platform feeding system are designed. Considering the flexible influence between screw nut and at both ends of its bearing contact surface and pre- tightening force,its flexible modal finite element is established. By 10 orders modal analysis,its vibration mode and natural frequency are obtained,and the maximum error between considering contact surface flexibility and pre- stress influence and without considering these factors is 24. 6%. The corresponding critical rotate speed of the first order natural frequency is obviously larger than the maximum rotate speed required by the screw. Therefore,the resonance will not occur in the system. Moreover,through the experimental test,its double nut positioning pre- tightening scheme and the computing method are verified. The methods and basis for the design of large- scale feed platform are provided.